2021
DOI: 10.1002/ece3.8208
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variations in a widely distributed Eastern Asian passerine cannot be consistently explained by ecogeographic rules

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Heat loss can occur from unfeathered areas such as the legs because they come into direct contact with solid substrates that have a higher specific heat than air, having higher heat exchange [92,93]. Similarly, other studies do not support Allen's rule for explaining geographical variation in beak size [11,24]. Multiple selective pressures might affect beak shape and size [94] because it is a multifunctional trait used to sing [95], in thermoregulation [25], and foraging [96], but also phylogenetic relationships [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heat loss can occur from unfeathered areas such as the legs because they come into direct contact with solid substrates that have a higher specific heat than air, having higher heat exchange [92,93]. Similarly, other studies do not support Allen's rule for explaining geographical variation in beak size [11,24]. Multiple selective pressures might affect beak shape and size [94] because it is a multifunctional trait used to sing [95], in thermoregulation [25], and foraging [96], but also phylogenetic relationships [29].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for Bergmann's rule is contradictory in birds, mammals and insects (e.g. [7,11,24,83,84]). A review study that considered the body geographical variation in 92 species of North American birds revealed that 42% of these species supported Bergmann's rule, 12% provided weak or ambiguous support, 16% showed no association between latitude or latitude, and in 29% of the species the patterns observed contradicted the rule [85].…”
Section: Brunneicapillus)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, much controversy remains about whether bird legs or tarsi (i.e. exposed leg parts) follow Allen's rule (as in [16,[19][20][21]). The most possible explanation lies in plastic physiological changes in the limbs, such as the countercurrent vascular arrangements, which minimize limb heat loss relative to bills [16,22], offsetting morphological changes.…”
Section: Introductionmentioning
confidence: 99%